Propuesta de un plan estratégico para la empresa “Coser Y Tejer De La Costa” en el municipio de fundación magdalena (2024)
As time goes by, companies are facing a widely competitive environment in which having a greater sales capacity is what will keep them standing. The number of entities that exist to meet people's needs is gigantic and each time they evolve more and more, the ability to adapt and take advantage of these opportunities offered by the economic environment will become the determining factor for success. Put in context, this thesis aims to develop a strategic plan for the company “Coser y Tejer de la costa” located in Fundación, Magdalena. Coser y Tejer de la Costa is a company that is focused on the manufacture and sale of textile products, it already had a track record in the traditional field, it has been understood that it needs a new strategic model to meet the current needs that people/customers need. This strategic plan seeks to provide the company with the necessary tools to position itself at the departmental level in order to search both internally and externally for each demand that the current market seeks or requests. In the development of this plan, a series of analyzes of the situation that the company is facing will be carried out, searching and identifying its strengths and weaknesses in the textile economic sector. We will then seek to establish both general and specific objectives necessary for correct functioning, this will allow us to guide the corresponding actions. This strategic plan will have a key analysis such as the search for Weaknesses, opportunities, Strengths and threats (SWOT), strategic management systems, what would be the needs to be covered, surveys of citizens of the sector; These strategies will be carefully selected depending on the moment depending on each need of Sewing and Knitting of the coast